Portable Biomass Gasifier Power Generation Using Non Edible Seed Cake - M Vivek; PK Srividhya; K Sujatha (Bulletin of Electrical Engineering and Informatics, 2015)
Non edible seeds are used most of the applications but the dehydration of seed cakes is too difficult. And the same time the seeds could not feed food as animal. Hence, to adopt various techniques it can be used for other applications. 1 ton crude oil yield from 3 tons of seeds and the remaining becomes seed cake. After oil extraction using screw press machine, seed cake still has 10 % to 15 % of oil.  Hence this is a good combustible material with calorific value of approximately 600 Kcal/m3 and the electrical output voltage 180 – 200 at the range of 3.00 -3.5 amps. This paper deals with the power generation from Jatropha seed cake using gasification technology.